2021
DOI: 10.3389/fpsyg.2021.673953
|View full text |Cite
|
Sign up to set email alerts
|

I Only Want Passionate Relationships: Are You Ready for That?

Abstract: Research shows the existence of a coercive dominant discourse that associates attraction with violence and influences the socialization processes of many girls and women. According to previous studies, the coercive dominant discourse constitutes a risk factor for gender violence, as men with violent attitudes and behaviors are socially presented as attractive and exciting while egalitarian and non-aggressive men are considered “not sexy.” Yet fewer evidences indicate that men acting from the New Alternative Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Torras-Gómez and colleagues (2019) first identified such fake narratives and their link to disdainful hookups and relationships, which is also confirmed in the current study. In this line, we observe characteristics of the CDD in the participants' narratives (Joanpere et al, 2021;Rodrigues-Mello et al, 2021) leading them or their friends to engage in disdainful hookups . In such hookups, the participants identify a lack of pleasure, as well as the fact that they engage in behaviors that they do not want or enjoy, but accept under the CDD (A. López de Torras-Gómez et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Torras-Gómez and colleagues (2019) first identified such fake narratives and their link to disdainful hookups and relationships, which is also confirmed in the current study. In this line, we observe characteristics of the CDD in the participants' narratives (Joanpere et al, 2021;Rodrigues-Mello et al, 2021) leading them or their friends to engage in disdainful hookups . In such hookups, the participants identify a lack of pleasure, as well as the fact that they engage in behaviors that they do not want or enjoy, but accept under the CDD (A. López de Torras-Gómez et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…Conveyed through different forms of entertainment (movies, shows, music…) and peer interactions, while the CDD presents violent masculinity models as the only attractive and desirable option, egalitarian models are deemed as convenient but lacking attractiveness and excitement (Gómez, 2015;Rodrigues-Mello et al, 2021;Villarejo et al, 2020;Villarejo-Carballido et al, 2022). In this way, the CDD leads to a double-standard frame of mind in which pleasure, fun, excitement and passion are separated from love, care, stability and egalitarianism (Gómez, 2015;Joanpere et al, 2021;Rios-González et al, 2018;Ruiz-Eugenio et al, 2021).…”
Section: State Of the Artmentioning
confidence: 99%
“…At this point we can also highlight that the comments collected in Digital Magazines, FilmAffinity and interviews not only reflect a diversity of opinions and tastes in film, but the information collected can also be linked to the language of ethics and the language of desire (Flecha et al, 2013;Joanpere et al, 2021;López de Aguileta et al, 2020;Melgar Alcantud et al, 2021;Merodio et al, 2020;Rios-González et al, 2018). We found that the comments in favor of the change in James Bond and criticism of the previous model it represented -mainly present in the film reviews and interviews -are mostly made from a language of ethics.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation can be found in the existing coercive discourse that promotes violence as more attractive and equality as less attractive (Racionero-Plaza et al, 2020;Torras-Gómez et al, 2019). Indeed, research has shown that the presence of the coercive discourse Racionero-Plaza, et al, 2020) socializes many individuals in the attractiveness towards violent masculinity models (Castro & Mara, 2014;Díez-Palomar et al, 2014;Flecha et al, 2013;Joanpere et al, 2021;Ruiz-Eugenio et al, 2021;Valls-Carol et al, 2021, Torras-Gómez et al, 2019. Indeed, research has shown that the presence of the coercive discourse Racionero-Plaza, et al, 2020) socializes many individuals in the attractiveness towards violent masculinity models (Castro & Mara, 2014;Díez-Palomar et al, 2014;Flecha et al, 2013;Joanpere et al, 2021;Ruiz-Eugenio et al, 2021;Valls-Carol et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation